pelecehan verbal (Catcalling) di Tinjau Dari Hukum Pidana: pelecehan verbal (Catcalling) di Tinjau Dari Hukum Pidana - Afrian, Fadillah; Susanti, Heni (Titian: Jurnal Ilmu Humaniora, 2022)
Abstract: With the passage of the Law on the Crime of Sexual Violence, known as the TPKS Law on April 12, 2022, it is considered capable of protecting the rights of victims of sexual harassment. The purpose and benefits of this research are to find out how criminal law views catcalling cases in Indonesia and to find out whether the existing regulations are sufficient to ensnare the perpetrators and achieve justice for the victims. The method used in writing this scientific paper is a normative study that focuses on positive legal norms governing sexual violence. The results of this study indicate that acts of verbal sexual harassment or known as catcalling are a form of decency crime that has the potential to become the beginning of sexual crimes such as rape and even human trafficking. In the Criminal Code (KUHP) catcalling is associated with immoral acts and obscenity. And clearly violates the laws and regulations Article 8 in conjunction with Article 34 and Article 9 in conjunction with Article 35 of Law no. 44/2008 concerning Pornography, and Article 5 of Law no. 12/2022 concerning Crimes of Sexual Violence. So that the conclusion is that this act has the potential to become a crime that has fulfilled the elements of a crime. The impact caused by this action includes the impact on the victim's psychological disorder, which leads to psychiatric disorders. So to prevent this action, special attention is needed both morally and legally to create legal certainty and justice for victims. Keywords: Catcalling, Crime, Immoral Acts